Formulasi Kue Pukis Berbahan Baku Tepung Gracilaria sp. Dengan Penambahan Tepung Rumput Laut Eucheuma cottonii - Aghitia Maulani; Yudi Prasetyo Handoko; Dwi Astrik Lisnayanti (Universitas Negeri Gorontalo, 2026)
Pukis cake is one of the moist cakes that is favored by the community. The utilization of seaweed as a functional food ingredient continues to grow in line with increasing public awareness of the importance of dietary fiber intake. This study aimed to analyze the effect of adding E. cottoniii flour on the quality of pukis cake that has been modified with Gracilaria. sp flour, as well as to determine the best formulation based on chemical, physical, microbiological, and hedonic test parameters. The research employed a Completely Randomized Design (CRD) with four treatments (F0, F1, F2, F3), involving the substitution of wheat flour with E. cottoniii flour at levels of 0%, 4%, 5%, and 6%, while the concentration of Gracilaria sp. flour was maintained at 3%. Parameters observed included proximate analysis, crude fiber, dietary fiber, viscosity, physical analysis (texture), microbiological testing (Total Plate Count), and hedonic testing by 30 panelists. The results showed that the best formulation was F2 (3% Gracilaria sp. and 5% E. cottoniii), with a protein content of 5.42%, dietary fiber of 4.18%, and highest scores of hedonic test including appearance, aroma, texture, taste, and overall preference. The addition of seaweed flour increased fiber content of 0.98% and improved the product’s texture without reducing consumer acceptability. These findings demonstrate the potential of utilizing local seaweed in diversifying functional food products based on traditional cakes.